2004
DOI: 10.1007/s00221-003-1637-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of reach-to-grasp movement in response to force perturbations

Abstract: This study examined how reach-to-grasp movements are modified during adaptation to external force perturbations applied on the arm during reach. Specifically, we examined whether the organization of these movements was dependent upon the condition under which the perturbation was applied. In response to an auditory signal, all subjects were asked to reach for a vertical dowel, grasp it between the index finger and thumb, and lift it a short distance off the table. The subjects were instructed to do the task as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
6
18
0
Order By: Relevance
“…The closure distance was approximately constant across all transport distance variations within a certain transport-speed condition (Fig. 4, Table 1), which is consistent to previous studies (Alberts et al 2000(Alberts et al ,2002Rand and Stelmach 2005;Rand et al 2004;Stelmach 1998,2001). This suggests that spatial information on the distance from the hand to the object plays a dominant role in triggering the aperture closure.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The closure distance was approximately constant across all transport distance variations within a certain transport-speed condition (Fig. 4, Table 1), which is consistent to previous studies (Alberts et al 2000(Alberts et al ,2002Rand and Stelmach 2005;Rand et al 2004;Stelmach 1998,2001). This suggests that spatial information on the distance from the hand to the object plays a dominant role in triggering the aperture closure.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, each subject produced a relatively constant closure distance across trials in relation to the total transport distance for each speed condition. Such stability in aperture closure distance in comparison to the aperture opening distance was in agreement with other previous studies (Alberts et al 2000(Alberts et al , 2002Rand and Stelmach 2005;Rand et al 2004;Stelmach 1998, 2001). However, across the range of speed conditions the closure distance changed (Fig.…”
Section: Aperture Closure Distancesupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the results from their mechanical perturbation study (1991 (1995), they suggested that the formation of grip aperture is adjusted to maintain the spatial relationship between the grasp and transport components. Similar implications were made in recent studies with neurologically healthy subjects (Alberts et al 2002;Rand and Stelmach 2005;Rand et al 2004;Stelmach 1998, 2001), and PD patients (Alberts et al 2000;Wang and Stelmach 2000).…”
Section: Introductionsupporting
confidence: 84%
“…This instruction was used to impose the maximum stress on the motor control system for examining the subject's capacity to coordinate the grasp and transport components under movement perturbations. Fast reach-to-grasp movements were also examined for similar reasons in some previous studies (Paulignan et al 1991a, b;Desmurget et al 1996;Rand et al 2004;Rand and Stelmach 2005). Before the perturbation set, the subjects were told that the perturbation would occur randomly across trials, but that they were to continue reaching for and grasping the target as quickly as possible in every trial.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%